Directive Illocutionary Acts Found in the Movies 21 And 22 Jump Street - Wisnu Adi Putra, I Putu; Sedeng, I Nyoman (Humanis, 2022)
This research is entitled Directive Illocutionary Acts found in The Movie 21 and 22 Jump Street. The purpose of this research is to identify the classification and the force of the speaker’s utterance that were found in the movie. The data were collected by applying the documentation and note taking techniques, and was analyzed by descriptive qualitative method. The speech acts theory was used to answer the problems of this research. It includes the types of directive illocutionary act proposed by Bach and Harnish (1979), and IFIDs proposed by Yule (1996). In this research, all of the direct directive acts were found. Meanwhile, only five types of indirect directive act were found except indirect questions. The illocutionary force of directive acts that were found are requesting, asking, forbidding, permitting, commanding, warning, prohibiting, ordering, and suggesting. The illocutionary force expressed by the speaker was considered felicitous if all the illocutionary force are fulfills